Global Infrastructure Projects as the Factor of National Economies's Development (the case of the Turkish Stream Gas Pipeline) - Marina Tolstel; Irina Anikina; Albina Gukova (Institute of Economic Research (IER), 2017)
The current stage of the economy's development differs from the past ones in that the role of global infrastructure projects acquires ever more importance and that forming and designing of such programs becomes now a much more sophisticated process, all of this has led to a situation where we have to revise our system of economic methods of the evaluation benefits of a global infrastructure project for all involved countries. The existing methods and ways of evaluation influence global infrastructure projects on socio-economic development of the participating countries are to be complemented by new approaches reflecting the market changes and the advent of new financial instruments and stratagems. The aim of the paper is to evaluate influence the global infrastructure project on socio-economic development of the participating countries in the globalized world economy with respect to its main economic and social consequences and synergy effects (the case of the Turkish Stream gas pipeline). The aim of the paper is to evaluate influence the global infrastructure project on socio-economic development of the participating countries in the globalized world economy with respect to its main economic and social consequences and synergy effects (the case of the Turkish Stream gas pipeline). The authors crated methodological approach to the study of infrastructure projects influence on socio-economic development of the members based on the identification, evaluation and prediction of the influence of factors external and internal environment on the changing economic potential of the infrastructure projects participants. Adequate investment in the development of infrastructure is an important driver of long-term economic growth. Traditionally, infrastructure has been funded mostly through public investment. However, in view of scarcity of budgetary resources and lack of capacity within the government to implement these ambitious programs, the strategy of the government relies significantly on promoting investment through a combination of public investment and private participation (include foreign investors). The presented methodological approach allows to define and early diagnose the global infrastructure projects which facilitate a multiplication effect within the national economy.
Keywords: B16; C18; F02; F21; F63; H54; 330; global infrastructure projects; economic development; international investment; globalization